Development of Linear Equations e-Learning Media by Integrating Geogebra in Google Sites - Rizqi, Muhammad Ainur; Sa’dijah, Cholis (Jurnal Pendidikan MIPA, 2023)
The purpose of this research is develop online linear equation learning media using Geogebra through Google sites. This is a research and development research that uses the Alessi and Trollip (2001) models. The development steps are: planning, design, and development. The instrument used in this study was student worksheets found on Google sites. This research was tested on 56 students of grade 8 MTsN 1 Malang City. The validation results show that this media is valid with a score of 85.6%. When the experiment was conducted on students, it showed that this media was practical with a score of 83.0% and effective with a score of 81.3%. This study also shows that through the steps of guided discovery learning: providing stimulation, problem statement, data collection, data processing, verification, and drawing conclusions students are able to construct concepts about straight-line equations independently. Keywords: learning media, linear equation, geogebra, google site. DOI: http://dx.doi.org/10.23960/jpmipa/v24i2.pp481-492